Positive electrode homogenizing process, positive electrode slurry and battery

By infiltrating the active substance in the solvent and gradually adding dispersant and conductive agent, combined with kneading and dispersing and post-treatment steps, the difficulty of agglomeration and dispersion of high specific surface area materials during homogenization is solved, and the uniformity of the positive electrode slurry is achieved and Viscosity stability improves the operability and quality of the coating.

CN119400855APending Publication Date: 2025-02-07FARASIS TECH (GANZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340017.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Materials with high specific surface area are very prone to agglomeration and difficulty in dispersion during homogenization, resulting in a rapid increase in the viscosity of the slurry and forming an uneven slurry.

Method used

By first infiltrating the active substance in the solvent, adding a dispersant and conductive agent, gradually stirring and dispersing, finally adding a dissolved binder, kneading and dispersing and post-treatment, the obtained positive electrode slurry has silky flow and no agglomeration. Characteristics of good particle and viscosity stability.

Benefits of technology

A uniform uniformity of the material with high specific surface area is achieved, which avoids powder removal caused by breaking the molecular chain of the binder, improves the solid content and processing operability of the positive electrode slurry, and ensures the uniformity and stability of the coating. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400855A_ABST
    Figure CN119400855A_ABST
Patent Text Reader

Abstract

The invention discloses a positive pole homogenizing process, a positive pole slurry and a battery, the positive pole homogenizing process comprises the following steps: infiltrating an active substance and a dispersant in a solvent for dispersion to obtain a first slurry; wherein the solid content of the active substance in the first slurry is # imgabs0 #, a conductive agent is added into the first slurry for dispersion, and second slurry is obtained; adding the dissolved binder into the second slurry, and kneading and dispersing to obtain third slurry; and carrying out post-treatment on the third slurry to obtain the positive electrode slurry. The slurry prepared by the invention is silky, good in fluidity, free of agglomerated particles, relatively good in viscosity stability, free of baking crack during coating, and free of powder falling and demolding of coating paired rollers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode homogenization process, a positive electrode slurry and a battery. Background Art

[0002] Materials with high specific surface areas are very difficult to homogenize. They are very easy to agglomerate and difficult to disperse during homogenization, causing the viscosity of the formed slurry to rise rapidly, resulting in a very uneven slurry. Summary of the invention

[0003] The main purpose of the present invention is to provide a slurrying process for a battery positive electrode, so as to solve the technical problem in the prior art that materials with high specific surface area are very easy to agglomerate and difficult to disperse during slurrying, resulting in a rapid increase in the viscosity of the formed slurry and causing uneven slurry.

[0004] In order to achieve the above object, the present invention provides a positive electrode homogenization process in a first aspect, comprising the following steps:

[0005] Step 1: The active material and the dispersant are immersed in a solvent and dispersed to obtain a first slurry, wherein the solid content of the active material in the first slurry is: Wherein A is the mass of the active substance, B is the mass of the solvent, ρ1 is the tap density of the active substance, and ρ2 is the true density of the active substance;

[0006] Step 2: adding a conductive agent to the first slurry for dispersion to obtain a second slurry;

[0007] Step 3: adding the dissolved binder to the second slurry for kneading and dispersion to obtain a third slurry;

[0008] Step 4: post-treating the third slurry to obtain a positive electrode slurry;

[0009] Furthermore, the active material is one of lithium manganese iron phosphate, lithium iron phosphate or sodium iron pyrophosphate.

[0010] Furthermore, the specific surface area of ​​the active material is 15 to 25 m 2 / g.

[0011] Furthermore, the step of soaking the active substance and the dispersant in a solvent to obtain a first slurry comprises:

[0012] The active substance and the dispersant are added to the solvent, and the mixture is stirred in multiple stages to obtain the first slurry; wherein the stirring speed and the stirring time in the latter stage are greater than the stirring speed and the stirring time in the previous stage.

[0013] Furthermore, the step of adding a conductive agent to the first slurry for dispersion to obtain a second slurry comprises:

[0014] The conductive agent is added to the first slurry, and the second slurry is obtained by stirring in multiple stages in sequence; wherein the stirring speed and stirring time in the latter stage are greater than the stirring speed and stirring time in the previous stage.

[0015] Furthermore, the step of post-processing the third slurry to obtain a positive electrode slurry comprises:

[0016] Performing a viscosity test on the third slurry to determine whether the viscosity of the third slurry is higher than a preset viscosity;

[0017] If yes, then add the solvent to perform orbital stirring, and then perform viscosity test;

[0018] If not, the third slurry is vacuumed and sieved to obtain the positive electrode slurry.

[0019] Furthermore, the mass percentages of the active material, the dispersant, the conductive agent and the binder are 94% to 96%: 0.3% to 0.7%: 1.0% to 3.0%: 2.5% to 3%.

[0020] Furthermore, the conductive agent includes a point-shaped conductive agent and a chain-shaped conductive agent, wherein the mass percentage of the point-shaped conductive agent is 0.5% to 2%; the mass percentage of the chain-shaped conductive agent is 0.5% to 1%.

[0021] A second aspect of the present invention provides a positive electrode slurry obtained by the positive electrode homogenization process described in any one of the above embodiments.

[0022] A third aspect of the present invention provides a battery, wherein the positive electrode of the battery is prepared using the positive electrode slurry in the above embodiment.

[0023] Beneficial effects:

[0024] A positive electrode homogenization process of the present invention first soaks the active material in a solvent, adds a dispersant to promote dispersion, reduces the agglomeration of the active material itself, then adds a conductive agent to reduce the agglomeration between the active material and the conductive agent, and finally adds a binder dissolved by the solvent. This can prevent the molecular chains in the binder from breaking due to long-term high-speed dispersion, causing powder loss and demolding during coating. The prepared slurry is smooth, has good fluidity, has no agglomerated particles, has good viscosity stability, has no cracking during coating, and has no powder loss and demolding on the coating roller. Furthermore, the solid content of the active material in the first slurry is: After the solid content is calculated using this formula, adding a certain amount of active material and solvent can ensure that the solvent just fills the gaps in the active material and completely soaks the active material, thereby avoiding the wet particles wrapping the dry particles to form large particle agglomerations during the homogenization process. It can also avoid agglomeration caused by lack of friction between the active materials due to too low solid content, and can also increase the solid content of the final positive electrode slurry, making the processing and coating operability better. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the process of positive electrode homogenization process in one embodiment of the present invention;

[0026] Figure 2 It is a curve diagram of the viscosity change of the positive electrode slurry in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0027] Figure 3 Schematic diagram of the morphology of the positive electrode slurry in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0028] Figure 4 Schematic diagram of the fineness of the positive electrode slurry in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0029] Figure 5 Schematic diagram of the coating state of the positive electrode slurry in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2;

[0030] Figure 6 Schematic diagram of scanning electron microscope of positive electrode slurry in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2.

[0031] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0032] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0033] At present, it is very difficult to homogenize materials with high specific surface areas. For example, lithium manganese iron phosphate (LMFP) is nano-sized due to the introduction of Mn. Mn has poor conductivity and lithium iron phosphate (LFP) is not very conductive either. Therefore, the material is usually nano-sized and carbon is coated on the surface of the material to improve the conductivity so that the material can be used. However, the modified LMFP is very easy to agglomerate and difficult to disperse during homogenization, causing the viscosity of the formed slurry to rise rapidly, resulting in a very uneven slurry.

[0034] Based on this, an embodiment of the present invention provides a positive electrode homogenization process, comprising the following steps:

[0035] Step 1: dispersing the active substance and the dispersant in a solvent to obtain a first slurry;

[0036] Step 2: adding a conductive agent to the first slurry for dispersion to obtain a second slurry;

[0037] Step 3: adding the dissolved binder to the second slurry for kneading and dispersion to obtain a third slurry;

[0038] Step 4: post-process the third slurry to obtain positive electrode slurry.

[0039] See also Figure 1 In the above embodiment, the active material is first soaked in the solvent, and the dispersant is added to promote dispersion, the agglomeration of the active material itself is reduced, and then the conductive agent is added to reduce the agglomeration between the active material and the conductive agent, and finally the binder dissolved by the solvent is added, which can avoid the molecular chain in the binder from breaking due to long-term high-speed dispersion, causing the coating to fall off and demold. The prepared slurry is smooth, has good fluidity, no agglomerated particles, and good viscosity stability. In addition, the entire homogenization process takes a short time, can improve production efficiency, and does not require other equipment except the planetary mixing tank, and has high operability.

[0040] In the above embodiment, the binder is pre-added to a certain amount of solvent to dissolve and disperse well, and then added to the second slurry after vacuuming to remove bubbles. Through dissolution and dispersion, the binder can be better mixed with the solvent to form a uniform binder solution, avoiding the phenomenon of lumps or unevenness when the binder is directly added to the second slurry. Preferably, the binder in the technical solution is PVDF5130, a common binder on the market, and the content of PVDF5130 in the binder solution is 5% to 12%.

[0041] Factors that affect the homogenization effect also include the solid content of the active substance during the dispersion and kneading process (the ratio of the mass of the active substance to the sum of the mass of the active substance and the solvent). If the solid content of the active substance is too high, the expected dispersion effect cannot be achieved. If the solid content of the active substance is too low, although a better dispersion effect can be obtained, the lack of friction between the active substances makes it easy to agglomerate, which is not conducive to subsequent coating applications and will lead to cracking or uneven surface density in the subsequent coating process. In addition, the long molecular chains of the binder are easily broken when dispersed at high speed for a long time, causing the electrode to lose powder.

[0042] Therefore, in one embodiment, the solid content of the active substance in the first slurry is: Wherein A is the mass of the active substance, B is the mass of the solvent, ρ1 is the tap density of the active substance, and ρ2 is the true density of the active substance.

[0043] The main factor affecting the homogenization effect is the solid content of the active substance (the ratio of the mass of the active substance to the sum of the mass of the active substance and the solvent) during the kneading and dispersion process. If the solid content of the active substance is too high, the expected dispersion effect cannot be achieved. If the solid content of the active substance is too low, although a better dispersion effect can be obtained, the lack of friction between the active substances makes them easy to agglomerate, which is not conducive to subsequent coating applications. Therefore, the solid content of the first slurry is set to

[0044]

[0045] Tap density and true density are material properties of active substances. The tap density of active substances refers to the mass per unit volume of the active substance powder in a container after being tapped under specified conditions. At this time, the active substance powder particles are rearranged to reduce the gaps between the particles, thereby achieving a tighter stacking state, that is, there are gaps between the particles, but the gaps are basically the smallest gaps possible; the true density of active substances refers to the actual mass of the solid substance per unit volume of the active substance in an absolutely dense state, that is, the density after removing the internal pores or gaps between the particles. It can be seen that It represents the relative porosity in the active substance. Taking this porosity as the solid content, adding a certain amount of active substance and solvent can ensure that the solvent fills the gaps in the active substance and completely soaks the active substance, thereby avoiding the wet particles wrapping the dry particles to form large particle agglomerations during the homogenization process. It can also avoid the agglomeration of active substances due to lack of friction caused by too low solid content, and can also increase the solid content of the overall finished slurry, making the processing and coating operability better.

[0046] In one embodiment, the active material is one of lithium iron manganese phosphate, lithium iron phosphate or sodium iron pyrophosphate. The active material can be a single crystal material or a spherical material. Lithium iron manganese phosphate, lithium iron phosphate or sodium iron pyrophosphate are commonly used positive electrode materials in batteries and have a high specific surface area. The tap density and true density of lithium iron manganese phosphate and sodium iron pyrophosphate are shown in Table 1. The selected solvent can be at least one of NMP (N-methylpyrrolidone), ethanol and acetone.

[0047] Table 1:

[0048]

[0049] In the above embodiment, the specific surface area of ​​the active material is 15 to 25 m 2 / g.

[0050] In one embodiment, the step of soaking the active material and the dispersant in a solvent to obtain a first slurry comprises:

[0051] The active substance and the dispersant are added to the solvent, and the mixture is stirred in multiple stages to obtain the first slurry; wherein the stirring speed and the stirring time in the latter stage are greater than the stirring speed and the stirring time in the previous stage.

[0052] In the above embodiment, the stirring speed of the first stage is relatively slow to prevent the powdered active substance from being lifted up and floating onto the wall of the planetary mixing tank before being dissolved in the solvent, and the stirring time is relatively short. The stirring speed of the second stage is relatively fast and the stirring time is relatively long, which is conducive to the rapid dispersion of the active substance. For example, the active substance and the dispersant are added to the solvent in the planetary mixing tank and dispersed in three stages in sequence. In the first stage, the revolution speed is 5-15 r / min and the stirring time is 5-10 min; in the second stage, the revolution speed is 20-30 r / min, the rotation speed is 1000-1500 r / min, and the stirring time is 10-20 min; in the third stage, the revolution speed is 35-45 r / min, the rotation speed is 2000-2500 r / min, and the stirring time is 60 min; to obtain the first slurry.

[0053] In one embodiment, the step of adding a conductive agent to the first slurry for dispersion to obtain the second slurry comprises:

[0054] The conductive agent is added to the first slurry, and the second slurry is obtained by stirring in multiple stages in sequence; wherein the stirring speed and stirring time in the latter stage are greater than the stirring speed and stirring time in the previous stage.

[0055] In the above embodiment, a certain amount of point-shaped conductive agent SP (carbon black) and chain-shaped conductive agent CNTs (carbon nanotubes) are added to the first slurry and stirred for 5-10 minutes at a low speed (revolution speed 5-15r / min, rotation speed 0r / min); stirred for 10-20 minutes at a medium speed (revolution speed 20-30r / min, rotation speed 1000-1500r / min); finally stirred for 60 minutes at a high speed (revolution speed 35-45r / min, rotation speed 2000-2500r / min) to obtain the second slurry. The dispersion speed should not be too high during high-speed stirring. If the dispersion speed is too high, the slurry will splash onto the wall and top of the mixing cylinder, affecting the ratio of active material to conductive agent. This embodiment can reduce the agglomeration between active material and conductive agent through three stages of stirring at low, medium and high speeds.

[0056] In one embodiment, the step of post-processing the third slurry to obtain a positive electrode slurry includes:

[0057] Performing a viscosity test on the third slurry to determine whether the viscosity of the third slurry is higher than a preset viscosity;

[0058] If yes, then add the solvent to perform orbital stirring, and then perform viscosity test;

[0059] If not, the third slurry is vacuumed and sieved to obtain the positive electrode slurry.

[0060] In the above embodiment, the obtained third slurry is first subjected to a viscosity test. If the viscosity is too high and unqualified, a solvent is added and the mixture is stirred in revolution to adjust the viscosity, and then the viscosity test is performed again until the viscosity test is qualified, and then the mixture is vacuumed to remove air bubbles and sieved to obtain the positive electrode slurry. Preferably, the slurry viscosity is set to be qualified when it is between 3000 and 10000 mpa·s, and preferably, the slurry viscosity is set to be qualified when it is between 6000 and 8000 mpa·s.

[0061] In one embodiment, the mass percentages of the active material, the dispersant, the conductive agent and the binder are 94% to 96%: 0.3% to 0.7%: 1.0% to 3.0%: 2.5% to 3%.

[0062] In the above embodiment, the conductive agent includes a point conductive agent and a chain conductive agent, wherein the mass percentage of the point conductive agent is 0.5% to 2%; the mass percentage of the chain conductive agent is 0.5% to 1%. The point conductive agent is such as SP (carbon black), and the chain conductive agent is such as CNTs (carbon nanotubes), carbon fiber, etc.

[0063] Another embodiment of the present invention provides a positive electrode slurry obtained by the positive electrode slurry process described in any of the above embodiments.

[0064] Another embodiment of the present invention provides a battery, wherein the positive electrode of the battery is prepared by using the positive electrode slurry in the above embodiment.

[0065] In order to more clearly illustrate the present invention, the following examples are given, but they do not limit the scope of the present invention in any way.

[0066] Example 1

[0067] Step 1: Use a planetary mixing cylinder to add 3.792kg of single crystal LMFP and 0.02kg of dispersant PVP K30 (polyvinyl pyrrolidone) to 1.448kg of NMP (N-methyl-2-pyrrolidone, N-Methyl-2-pyrrolidone) solvent to form a mixed slurry with a solid content of 72.3%. The mixed slurry is stirred at a low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stirred at a medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stirred at a high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain a first slurry.

[0068] Step 2: Add 0.06kg of point-shaped conductive agent SP and 0.667kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stir at high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain the second slurry.

[0069] Step 3: Add 1 kg of 10% binder solution prepared in advance to the second mixed slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0070] Step 4: Add 0.4 kg NMP to adjust the viscosity, evacuate and pass through a 150-mesh sieve to obtain a positive electrode slurry. The obtained positive electrode slurry has a viscosity of 6750 mpa·s, a fineness of 35 μm, a solid content of 53.5%, is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating.

[0071] Example 2

[0072] Step 1: Use a planetary mixing cylinder to add 3.84 kg of spherical LMFP and 0.012 kg of dispersant PVP K30 to 1.888 kg of NMP solvent to form a mixed slurry with a solid content of 67.1%. The mixed slurry is stirred at a low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stirred at a medium speed (revolution 25 r / min, rotation 1500 r / min) for 10 minutes; finally, stirred at a high speed (revolution 40 r / min, rotation 2500 r / min) for 60 minutes to obtain a first slurry;

[0073] Step 2: Add 0.012kg of point-shaped conductive agent SP and 0.667kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stir at high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain the second slurry.

[0074] Step 3: Add 1.08 kg of 10% concentration binder solution prepared in advance to the second slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0075] Step 4: Add 0.12 kg NMP to adjust the viscosity and pass through a 150-mesh sieve to obtain a positive electrode slurry. The obtained positive electrode slurry has a viscosity of 7469 mpa·s, a fineness of 35 μm, a solid content of 52.5%, is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating.

[0076] Example 3

[0077] Step 1: Use a planetary mixing tank to add 3.76 kg of sodium iron pyrophosphate and 0.016 kg of dispersant PVP K30 to 1.744 kg of NMP solvent to form a mixed slurry with a solid content of 68.4%. The mixed slurry is stirred at a low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stirred at a medium speed (revolution 25 r / min, rotation 1500 r / min) for 10 minutes; finally, stirred at a high speed (revolution 40 r / min, rotation 2500 r / min) for 60 minutes to obtain a first slurry;

[0078] Step 2: Add 0.092kg of point-shaped conductive agent SP and 0.667kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stir at high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain the second slurry.

[0079] Step 3: Add 1.04 kg of 10% concentration binder solution prepared in advance to the second slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0080] Step 4: Add 0.292 kg NMP to adjust the viscosity and pass through a 150-mesh sieve to obtain a positive electrode slurry. The positive electrode slurry has a viscosity of 6814 mpa·s, a fineness of 35 μm, and a solid content of 52.2%. It is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating.

[0081] Example 4

[0082] Step 1: Use a planetary mixing cylinder to add 3.76 kg of single crystal LMFP active material and 0.024 kg of dispersant PVP K30 to 1.449 kg of NMP solvent to form a mixed slurry with a solid content of 72.3%. The mixed slurry is stirred at a low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stirred at a medium speed (revolution 25 r / min, rotation 1500 r / min) for 10 minutes; finally, stirred at a high speed (revolution 40 r / min, rotation 2500 r / min) for 60 minutes to obtain a first slurry;

[0083] Step 2: Add 0.068kg of point-shaped conductive agent SP and 0.667kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stir at high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain the second slurry.

[0084] Step 3: Add 1.2 kg of 10% concentration binder solution prepared in advance to the second slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0085] Step 4: Add 0.349 kg to adjust the viscosity and pass through a 150-mesh sieve to obtain a positive electrode slurry. The positive electrode slurry has a viscosity of 6414 mpa·s, a fineness of 30 μm, and a solid content of 53.0%. It is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating.

[0086] Example 5

[0087] Step 1: Use a planetary mixing cylinder to add 3.764 kg of single crystal LMFP and 0.028 kg of dispersant PVP K30 to 1.453 kg of NMP solvent to form a mixed slurry with a solid content of 72.3%. The mixed slurry is stirred at a low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stirred at a medium speed (revolution 25 r / min, rotation 1500 r / min) for 10 minutes; finally, stirred at a high speed (revolution 40 r / min, rotation 2500 r / min) for 60 minutes to obtain a first slurry;

[0088] Step 2: Add 0.08 kg of point-shaped conductive agent SP and 0.667 kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stir at medium speed (revolution 25 r / min, rotation 1500 r / min) for 10 minutes; finally, stir at high speed (revolution 40 r / min, rotation 2500 r / min) for 60 minutes to obtain the second slurry.

[0089] Step 3: Add 1 kg of 10% concentration binder solution prepared in advance to the second slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0090] Step 4: Add 0.527 kg NMP to adjust the viscosity and pass through a 150-mesh sieve to obtain a positive electrode slurry. The positive electrode slurry has a viscosity of 3570 mpa·s, a fineness of 35 μm, and a solid content of 53.2%. It is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating. However, the slurry viscosity is too low and the coating surface density is unstable.

[0091] Comparative Example 1

[0092] Step 1: Use a planetary mixing cylinder to add 3.792kg of single crystal LMFP and 0.02kg of dispersant PVP K30 (polyvinyl pyrrolidone) to 1.9kgNMP (N-methyl-2-pyrrolidone, N-Methyl-2-pyrrolidone) solvent to form a mixed slurry with a solid content of 66.7%. The mixed slurry is stirred at a low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stirred at a medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stirred at a high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain a first slurry.

[0093] Step 2: Add 0.06kg of point-shaped conductive agent SP and 0.667kg of chain-shaped conductive agent CNTs with a solid content of 4.2% to the first slurry, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 1500r / min) for 10 minutes; finally, stir at high speed (revolution 40r / min, rotation 2500r / min) for 60 minutes to obtain the second slurry.

[0094] Step three: add 1 kg of 10% concentration binder solution prepared in advance to the second mixed slurry, stir at high speed (revolution 40 r / min, rotation 0 r / min) for 10 minutes, and then disperse and knead at high speed (revolution 40 r / min, rotation 5000 r / min) for 120 minutes to obtain the third slurry.

[0095] Step 4: Add 1.307 kg NMP to adjust the viscosity, evacuate and pass through a 150-mesh sieve to obtain a positive electrode slurry. The obtained positive electrode slurry has a viscosity of 10075 MPa·s, a fineness of 35 μm, a solid content of 50.8%, is easy to sieve, the static viscosity of the slurry is stable for 48 hours, and there is no cracking of large particles during coating.

[0096] Comparative Example 2

[0097] Step 1: Use a planetary mixing tank to add 0.1kg PVDF5130 dry powder into 1.9kg NMP solvent, stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 2500r / min) for 10 minutes; finally stir at high speed (revolution 40r / min, rotation 5000r / min) for 120 minutes to completely dissolve the PVDF dry powder and evacuate to obtain a PVDF solution.

[0098] Step 2: Add 0.06 kg of point-shaped conductive agent SP to the PVDF solution and stir at low speed (revolution 10 r / min, rotation 0 r / min) for 5 minutes; then stir at medium speed (revolution 25 r / min, rotation 2500 r / min) for 10 minutes; finally stir at high speed (revolution 40 r / min, rotation 5000 r / min) for 60 minutes, add 0.667 kg of CNTs with a solid content of 4.2% and repeat the above steps of high-speed stirring (revolution 40 r / min, rotation 5000 r / min, stirring for 60 minutes) to obtain the conductive glue.

[0099] Step three: add 3.792kg spherical LMFP active material and 0.02kg PVP K30 to the conductive glue and stir at low speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 10r / min, rotation 0r / min) for 5 minutes; then stir at medium speed (revolution 25r / min, rotation 2500r / min) for 10 minutes; finally stir at high speed (revolution 40r / min, rotation 5000r / min) for 120 minutes, and finally gradually add a total of 1.16kgNMP to adjust the viscosity so that the slurry has fluidity. The slurry is difficult to pass through a 150-mesh sieve. The viscosity of the positive electrode slurry is 11257mpa·s, the fineness is greater than 100μm, the solid content is 50.4%, the static viscosity of the slurry rises rapidly in 48h, and there are large particles on the surface of the coated electrode.

[0100] The static viscosity changes of the slurry stability obtained in the above examples and comparative examples are as follows: Figure 2 , the slurry state is as follows Figure 3 , the slurry fineness is Figure 4 , coating status such as Figure 5 , coated electrode SEM Figure 6 The test data of the slurries of various embodiments and comparative examples are shown in Table 2.

[0101] Table 2:

[0102]

[0103] Figure 2 In the static process of the positive electrode slurry after preparation, the viscosity of the slurry of Comparative Examples 1 and 2 increased rapidly from about 10000 mpa.s to nearly 100000 mpa.s within 0-12 hours, and then remained stable, while the viscosity of the slurry of Examples 1-5 remained within 20000 mpa.s within 0-12 hours, with only a small increase. It can be seen that the viscosity of Examples 1-5 did not change much within 48 hours of static standing, and the stability was much higher than that of the two comparative examples;

[0104] Figure 3 3a~3e are schematic diagrams of the morphology of the positive electrode slurry in Examples 1~5, and 3f~3g are schematic diagrams of the morphology of the positive electrode slurry in Comparative Examples 1~2; the positive electrode slurry in 3a~3e is silky, has good fluidity, and has no agglomerated particles, while the positive electrode slurry in 3f~3g is viscous and gel-like, has poor fluidity, and has obvious agglomerated particles on the surface of the slurry compared to the positive electrode slurry in 3a~3e.

[0105] Figure 4 4a to 4e are schematic diagrams of the fineness of the positive electrode slurry in Examples 1 to 5, and 4f to 4g are schematic diagrams of the fineness of the positive electrode slurry in Comparative Examples 1 to 2. The fineness of the positive electrode slurry in 4a to 4e is about 35 μm, while the fineness of the positive electrode slurry in 4f to 4g is above 100 μm, which shows that the fineness of the positive electrode slurry prepared by the method of the present application is smaller.

[0106] Figure 5 5a to 5e are schematic diagrams of the coating state of the positive electrode slurry in Examples 1 to 5, and 5f to 5g are schematic diagrams of the coating state of the positive electrode slurry in Comparative Examples 1 to 2. The interfaces in 5a to 5e are clean, without large particle agglomeration, cracking, etc., while in 5f to 5g, cracking, large particle agglomeration, etc., it can be seen that the positive electrode slurry prepared by the method of the present application is more evenly coated, and no agglomeration, cracking, etc. occur after drying.

[0107] Figure 66a to 6e are schematic diagrams of scanning electron microscopes of the positive electrode slurries in Examples 1 to 5, and 6f to 6g are schematic diagrams of scanning electron microscopes of the positive electrode slurries in Comparative Examples 1 to 2. No large agglomerated particles were observed in 6a to 6e, and the particles were evenly distributed, while large particles agglomerated in 6f to 6g. For example, the bright area in the middle and upper part of 6f is a large particle formed by the agglomeration of single crystal LMFP, and the large particle in the middle and upper part of 6g is a large particle formed by the agglomeration of spherical LMFP. It can be seen that the positive electrode slurry prepared by the method of the present application has a uniform particle distribution and basically no large particle agglomeration.

[0108] pass Figure 3 to Figure 6 It shows that changing the order of adding active substances, binders and conductive agents, as well as controlling the amount of raw materials used have a good effect on the dispersion of the homogenization process.

[0109] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A positive electrode homogenization process, characterized in that: The following steps are involved: Step 1: The active material and the dispersant are immersed in a solvent and dispersed to obtain a first slurry, wherein the solid content of the active material in the first slurry is: Wherein A is the mass of the active substance, B is the mass of the solvent, ρ1 is the tap density of the active substance, and ρ2 is the true density of the active substance; Step 2: adding a conductive agent to the first slurry for dispersion to obtain a second slurry; Step 3: adding the dissolved binder to the second slurry for kneading and dispersion to obtain a third slurry; Step 4: post-process the third slurry to obtain positive electrode slurry.

2. The positive electrode homogenization process according to claim 1, characterized in that: The active material is one of lithium manganese iron phosphate, lithium iron phosphate or sodium iron pyrophosphate.

3. The positive electrode homogenization process according to claim 1, characterized in that: The specific surface area of ​​the active material is 15 to 25 m 2 / g.

4. The positive electrode homogenization process according to claim 1, characterized in that: The step of soaking the active substance and the dispersant in a solvent to obtain a first slurry comprises: The active substance and the dispersant are added to the solvent, and the mixture is stirred in multiple stages to obtain the first slurry; wherein the stirring speed and the stirring time in the latter stage are greater than the stirring speed and the stirring time in the previous stage.

5. The positive electrode homogenization process according to claim 1, characterized in that: The step of adding a conductive agent to the first slurry for dispersion to obtain a second slurry comprises: The conductive agent is added to the first slurry, and the second slurry is obtained by stirring in multiple stages in sequence; wherein the stirring speed and stirring time in the latter stage are greater than the stirring speed and stirring time in the previous stage.

6. The positive electrode homogenization process according to claim 1, characterized in that: The step of post-processing the third slurry to obtain a positive electrode slurry comprises: Performing a viscosity test on the third slurry to determine whether the viscosity of the third slurry is higher than a preset viscosity; If yes, then add the solvent, perform orbital stirring, and then perform viscosity test; If not, the third slurry is vacuumed and sieved to obtain the positive electrode slurry.

7. The positive electrode homogenization process according to claim 1, characterized in that: The mass percentages of the active material, the dispersant, the conductive agent and the binder are 94% to 96%: 0.3% to 0.7%: 1.0% to 3.0%: 2.5% to 3%.

8. The positive electrode homogenization process according to claim 7, characterized in that: The conductive agent includes a point-shaped conductive agent and a chain-shaped conductive agent, wherein the mass percentage of the point-shaped conductive agent is 0.5% to 2%; the mass percentage of the chain-shaped conductive agent is 0.5% to 1%.

9. A positive electrode slurry, characterized in that: The method is obtained by the positive electrode homogenization process according to any one of claims 1 to 8.

10. A battery, characterized in that: The positive electrode of the battery is prepared by using the positive electrode slurry according to claim 9.